SAPLING protocol for obtaining baseline data on value chain performance and inclusion, as well as innovation use by service providers, applicable to the 15 SAPLING livestock value chains - Marshall, Karen; Poole, Elizabeth J.; Teufel, Nils; Njehu, Alice; Baltenweck, Isabelle (International Livestock Research Institute, 2022)
This manual is a protocol developed as part of the monitoring, evaluation, and learning (MEL) activities for the One CGIAR Initiative Sustainable Animal Productivity for Livelihoods, Nutrition and Gender Inclusion (SAPLING). It describes the processes for obtaining baseline data on value chain performance and inclusion, as well as innovation use by service providers, which will be applied for each of SAPLING’s 15 focal livestock value chains. The actual data collection tools are annexed.